Single-step genome-wide association study of milk somatic cell scores across multi-cattle breeds in Ethiopia - Chernet, T.F.; Tarekegn, G.M.; Okeyo Mwai, Ally; Meseret, Selam; Mrode, Raphael A.; Negussie, E.; Bedada, Z.E.; Gebreyohanes, Gebregziabher; Ekine-Dzivenu, Chinyere C.; Tera, A.; Tessema, T.S. (MDPI, 2025)
Mastitis, an inflammation of the bovine mammary gland, reduces dairy productivity and poses significant health risks to Ethiopian dairy cattle. This study aimed to identify genomic regions associated with milk somatic cell score (SCS) and estimate its genetic parameters. The dataset included 1647 phenotypic cows, 6964 genotyped animals, and 39,976 single nucleotide polymorphism (SNP) markers. A single-step genome-wide association study (ssGWAS) was conducted, accounting for fixed effects of parity, genomic breed composition, altitude, and lactation stage, and random effects of herd-year-calving-season and permanent environment. Genetic variance using 20 adjacent SNPs sliding windows explaining ≥1% of the total genetic variance were used for candidate genes and quantitative trait loci (QTL) identifications. The estimated heritability of SCS was 0.11 ± 0.06. Genomic regions on BTA 15, 19, and 26 were identified associated with SCS, encompassing 116 genes, including MPP7, MPP8, MMP13, BIRC2, BIRC3, BTRC, SRSF1, and MPO, which are involved in immunity, inflammation, apoptosis, antimicrobial defense, and tissue remodeling. Gene enrichment analysis revealed that the genes are involved collagen catabolic process and IL-17 signaling pathway. These findings provide insights into genomic regions that could be targeted in genomic selection to improve mastitis resistance in Ethiopian dairy cattle.